The Influence of Gobak Sodor Traditional Games towards Students’ Agility and Teamwork - Ai Faridah; Dian Permana; Arief Adhitia Hamzah; Tufail Ibrahim Said (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Traditional sports are a type of sport that exists in a certain area, based on the culture of that area. Traditional games are physical activities that are carried out consciously and deliberately and use traditional rules that have been passed down from generation to generation by the community. The traditional game that researchers used to conduct this research was the traditional game gobak sodor. The gobak sodor game is a team sport consisting of more than two people in one group. The aim of this research is to describe the influence of the traditional game Gobak Sodor on students' agility and cooperation so that there is no need for a comparison class (control class) so that conclusions can be drawn whether there is an influence of the traditional game Gobak Sodor on students' agility and cooperation. The sample in this study was 29 students at SDI Imam Ahmad Bin Hanbal taken using purposive sampling technique. This research uses a quantitative approach with an experimental research method, one group pretest posttest design. Shuttle run test for agility, observation of cooperation to determine the level of cooperation and documentation. Statistical calculations using SPSS 26 paired sample t test. The data shows that there is a significant influence of traditional gobak sodor on the agility of fourth grade elementary school students.